Pengaruh Kepemimpinan, Motivasi Kerja & Budaya Kerja terhadap Kepuasan Pegawai Di SMK NU 2 Soko, Glagah Lamongan, - Septiawati, Sofia Tri (CV ODIS, 2024)
This research aims to test and analyze the influence of leadership, work motivation, and work culture on employee satisfaction at SMK NU 2 Soko. Data was collected by distributing questionnaires to 32 SMK NU 2 Soko employees. Data analysis in this study used SPSS assistance. The sampling technique used is the census method, and the data testing techniques used in this study include the validity test with factor analysis and reliability testing with Cronbach Alpha. Proving the research hypothesis with the T Test and F. Test The results of the analysis show that leadership, motivation, and work culture have a positive effect on employee satisfaction